The Integration of Technology in Ratio and Proportion Learning: A Systematic Literature Review - Lucy Asri Purwasi; Nyimas Aisyah; Yusuf Hartono; Budi Mulyono (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2026)
Ratio and proportion are fundamental topics in mathematics taught from elementary school to college, with significant relevance in education and everyday life. This study aims to systematically review technology-based innovations in ratio and proportion learning over the past 13 years. A Systematic Literature Review method was used to identify, synthesize, and analyze 23 journals published between 2012 and 2025, utilizing the Scopus and Google Scholar databases. This literature review consists of three main stages: planning, implementation, and reporting the review. The analysis results show that the most dominant type of technology used is Game-Based Learning, followed by Web-Based Platforms. These technologies have significantly contributed to improving mathematical skills such as proportional reasoning, problem-solving, critical thinking, creativity, and communication, especially among elementary and secondary school students. Proportional reasoning was noted as the key skill most developed through the application of these technologies. Based on these findings, further research is recommended to design interventions that integrate technology and local culture, employ contextual and realistic approaches, and also consider affective domains, such as self-confidence, motivation, and values, which are still under-researched but play a crucial role in technology use. This is expected to significantly contribute to creating more meaningful and accessible learning experiences.